The Influence of Intellectual Coercive Leadership Based on Trust on Human Resource Performance in Indonesia’s Creative Economy Sector - Ratih Pratiwi; Raflian Alviki Radisha; Jaka Apriyani (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the effectiveness of the Amanah Coercive Intellectual Leadership (ACIL) concept in improving human resource (HR) performance in Indonesia’s creative economy sector. ACIL combines coercive leadership, intellectual stimulation, and the value of amanah rooted in local wisdom. Despite the high potential of creative cities such as Bandung, Yogyakarta, and Denpasar, many industry players face challenges in HR management, including low integrity and high employee turnover. This study uses a quantitative explanatory approach with the Partial Least Squares-based Structural Equation Modeling method to examine the relationship between trust, coercive leadership, intellectual stimulation, and HR performance. Data were collected from 190 respondents in five creative cities through an online questionnaire. The results indicate that trust significantly influences coercive leadership, intellectual stimulation, and directly improves HR performance. Coercive leadership is also proven to significantly improve performance, while intellectual stimulation does not show a significant effect. In addition, coercive leadership mediates the relationship between trust and HR performance, while intellectual stimulation does not. These findings underscore the importance of building trust and implementing a coercive, trust-based leadership style to support HR performance, as well as the need for stronger ecosystem support for the realization of creative ideas.